ANALYSIS OF THE CONCEPT OF UJRAH ON THE HABIT OF EXCHANGING MONEY BEFORE EID AL-FITR IN BANJAR SOCIETY FROM THE PERSPECTIVE OF HIZFH AL-MAL - Fateya Rahman, Ahmad Reysa; Kuratulaini, Kuratulaini; Syahrida, Laily (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The custom of the Banjar people when approaching Eid al-Fitr is to exchange money, this habit aims to break one large denomination of money into several small denominations to brokers, and in paying for this service brokers usually set a tariff of 10%-20% depending on the nominal as a form of ujrah. The method used in this research is descriptive normative law with a qualitative approach in analysing the concept of money exchange ujrah in Banjar society in the perspective of Hizfh al-mal. The results of this study indicate that the habit of exchanging money in the Banjar community can facilitate the community and shorten the time in its activities, compared to exchanging money at an official bank. The service fee set by brokers or sellers is relevant to the concept of ujrah sharia and does not contradict one of the focussed maqasid sharia, namely hifz al-mal.